Peranan Akuntansi Forensik dalam Mengungkap Gratifikasi dan Penyalahgunaan Wewenang : Studi kasus : Lembaga Pembiayaan Ekspor Indonesia dan Bandung Smart City - Tiara Marcella Ruskito,; Viona Eka Putri Mardiono,; Tries Ellia Sandari, (Jurnal Mutiara Ilmu Akuntansi, 2024)
This research aims to examine the role of forensic accounting in detecting and exposing acts of graft and abuse of authority, focusing on the case of the Indonesian Export Financing Agency (LPEI) and the Bandung Smart City project. Forensic accounting offers an in-depth law-based investigative approach, which enables the disclosure of patterns of financial manipulation as well as weaknesses in internal controls. This research uses a qualitative method through a literature review of relevant journals, books, and literature. The results show that forensic accounting is not only effective in uncovering financial irregularities, but also contributes to increasing transparency and accountability in the public sector. Forensic accounting has proven to be a strategic tool both in the investigation process and fraud prevention, so that it can support better state financial governance.